FUNGSI BADAN PENGAWAS OBAT DAN MAKANAN TERHADAP PEREDARAN MAKANAN IMPOR DALAM MEWUJUDKAN PERLINDUNGAN KONSUMEN (Qawanin Jurnal Ilmu Hukum, 2023)
AbstrackThis study aims to determine the function of the Food and Drug Supervisory Agency on the circulation of imported food in realizing consumer protection. Knowing the factors that influence the effectiveness of the function of the Food and Drug Supervisory Agency on the circulation of imported food in realizing consumer protection. This study uses empirical research methods by reviewing and analyzing the functions and factors of the Food and Drug Supervisory Agency on the circulation of imported food in realizing consumer protection. The result of this study that The Function Of The Food and Drug Supervisory Agency on the circulation of imported food is to (1) Policy Making (2) Implementation Of Drug And Food Contro (3) Prosecution For Violations (4) Authority. The factor of the lack or still low legal awareness of consumers to make complaints or reports to both national consumer protection agencies and non-governmental consumer protection institutions will certainly also affect the quality of supervision by BBPOM. The recommendation of this research is that it is hoped that BPOM should be more active in supervising Imported Food circulating in the community. The need re-enhanced cooperation between state institutions related to control of imported food. These state institutions include the Directorate of General of Customs and Excise, Ministry of Trade, Ministry of Health, Ministry of Industry, POLRI, and many other state institutions who can be invited to work together to monitor the incoming imported food to Indonesia.Abstrak:Penelitian ini bertujuan untuk mengetahui fungsi Badan Pengawas Obat dan Makanan terhadap peredaran makanan impor dalam mewujudkan perlindungan. Mengetahui faktor-faktor yang berpengaruh terhadap efektivitas fungsi Badan Pengawas Obat dan Makanan terhadap peredaran makanan impor dalam mewujudkan perlindungan konsumen. Penelitian ini menggunakan metode penelitian empiris dengan cara mengkaji dan menganalisis fungsi serta faktor Badan Pengawas Obat dan Makanan terhadap peredaran makanan Impor dalam mewujudkan perlindungan konsumen. Hasil penelitian ini menunjukkannFungsi Badan Pengawas Obat dan Makanan terhadap peredaran makanan impor adalah Penyusunan Kebijakan (2) Pelaksanaan Pengawasan Obat dan Makanan (3) Penindakan Terhadap Pelanggaran (4) Wewenang. Faktor kurangnya atau masih rendahnya kesadaran hukum konsumen untuk melakukan pengaduan atau pelaporan baik kepada lembaga perlindungan konsumen nasional maupun lembaga perlindungan konsumen swadaya masyarakat tentu juga akan berpengaruh kepada